Worm Infestation (Homoeopathy for All, 2021)
whipworms,  hookworms,  When worms like roundworms,  tapeworms and flukes affect the intestines and other parts of the body, Worm infestations happens. No symptom is shown in a patient with a mild infestation but some may have itching around the anal are a  Worm infestation is one of the most common finding among children especially in developing countries. There are different kinds of worms which are pathogenic to human body. The most common  Ascariasis, Trichuriasis, Hookworm, and Enterobiasis which  tra
Keywords: hookworms; roundworms; Ascariasis